2000
DOI: 10.1111/j.1365-2141.2000.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone sialoprotein mRNA and protein expression in human multiple myeloma cell lines and patients

Abstract: Summary. Bone sialoprotein (BSP) is a glycoprotein essentially found in mineralizing connective tissues. We have recently demonstrated that BSP is ectopically expressed by carcinomas that metastasize to bone with high frequency. Multiple myeloma (MM) is characterized by the localization of tumour plasma cells in the bone marrow. In this study, BSP expression was evaluated in human myeloma cell lines and in bone marrow aspirates and one ascites fluid from MM patients. BSP was detectable in conditioned media of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…It was suggested that BSP protein expression in primary resected NSCLC was strongly associated with BM progression and could be useful in identifying patients at high risk of developing BM. Bellahcene et al [7,9] also reportedthatBSPwashighlyexpressedindifferenthistologicaltypesoflungcancerbothinproteinandmRNAanalysis.…”
Section: Serum Levels Of Bsp Cea and Cyfra 21-1mentioning
confidence: 99%
“…It was suggested that BSP protein expression in primary resected NSCLC was strongly associated with BM progression and could be useful in identifying patients at high risk of developing BM. Bellahcene et al [7,9] also reportedthatBSPwashighlyexpressedindifferenthistologicaltypesoflungcancerbothinproteinandmRNAanalysis.…”
Section: Serum Levels Of Bsp Cea and Cyfra 21-1mentioning
confidence: 99%
“…Measurement of cell surface receptors and protein expression (19) and genetic profiling of the primary tumor may be informative, but conference participants were not optimistic that such approaches would provide clinically useful information in the next 5 years. More reliable prediction will require study of the target organ for metastasis rather than the primary lesion, as well as a better understanding of the bone microenvironment and the interactions between tumor cells, bone cells, and marrow stromal cells.…”
Section: Preserving Normal Bone Healthmentioning
confidence: 99%